Editorial – Another State of Mind: Rethinking the State to understand the ‘Return of the State’ - Palano, Damiano (Soft Power, 2024)
As Don Gaetano, one of the characters in Leonardo Sciascia’s novel Todo Modo, sarcastically was, many scholars of political phenomena could today be surprised by the news that the state is not dead yet. In fact, the whole of the twentieth century was marked by a series of recurring diagnoses that heralded the disappearance of the state, or at least its ‘crisis’. It re-emerged in the era of globalisation, the belief that the state was affected by an obsolescence destined to lead it to death cyclically spanned the entire twentieth century, even if, from time to time, the accents changed and the causes were seen in different phenomena. In 1907, in the pages of Le Mouvement Socialiste, Edouard Berth —a supporter of revolutionary syndicalism and follower of the philosophy of George Sorel— emphatically greeted the death ‘of this fantastic, prodigious being who had such a colossal place in history’ — the state (quoted in Schmitt, 1972, p. 123). This diagnosis was shared by many scholars at the time. In 1908, for example, Léon Duguit wrote that ‘the personal and sovereign state is dead or is about to die’ (Duguit, 1911, p. 144). The following year, in his famous inaugural address on The Modern State and its Crisis, Santi Romano presented —albeit with different accents— a largely similar reading. After retracing the historical events that had led to the formation of the modern state, the Sicilian jurist formulated a rather gloomy diagnosis of its destiny: the state ‘which emerged from the French revolution’, wrote Romano, was ‘too simple’ (1950, p. 318), and the parliamentary system built during the 19th century, due to this genetic limit, was totally inadequate in the face of the need to guarantee the representation of new economic and social groups